THE LEGAL LIABILITY OF ONLINE DRIVER FOR PASSENGERS ACCIDENT IN CONSUMER PROTECTION LAW - Purba, Mariah Sonanggok; Sinaga, Fixma Raju (UNISSULA, 2021)
Online motorcycle taxis have become a favorite public transportation for some people because they are flexible in their activities, can reach places that are not passed by public transportation such as city transportation (public transport), buses, or other types of four-wheeled public transportation. One of the losses experienced by passengers or motorcycle taxi service users is the occurrence of accidents caused by the mistakes of motorcycle taxi drivers. Legal certainty to provide protection to consumers in the form of protection of consumer rights, so that business actors do not act arbitrarily which always harms consumers. The research method used is normative juridical. The results of this study are that most of the Indonesian online motorcycle taxi companies use motorbikes as their means of transportation and receive payment for the services provided, not in accordance with what is stipulated in UULAJ and Government Regulation Number 74 of 2014 concerning Road Transportation. In order to operate the transportation of people not on a route using a public motorized vehicle, the public transportation company is required to have a license to operate the transportation of people not on a route which must meet the requirements. Legal protection for online motorcycle taxi passengers when an accident occurs is divided into 2, namely preventive and repressive legal protection.